A case of Jack Russel Terrier scavenging: Images and three dimensional models for forensic interpretation. (July 2019) - De-Giorgio, Fabio; Grassi, Simone; Berketa, John William
Abstract: Distinguishing between ante-mortem and post-mortem domestic dog injuries is fundamental in order to correctly find the cause of the death. Although fatal aggressions are chiefly perpetrated by pit bull-type dogs, small dogs are responsible for a significant share of animal bites and can cause high-degree injuries. On the other side, indoor and outdoor scavenging can hinder forensic investigation, consuming parts of the body where crucial forensic features like bruises and wounds have been inflicted. In the case we present, a man died after falling down his house stairs because of a traumatic intracranial haemorrhage. His dog, a Jack Russel Terrier, scavenged a significant portion of his facial superficial and deep tissues, suggesting to the investigators the hypothesis of a brutal aggression. In this paper, we showed how the application of advanced 3D processing and modelling techniques can give a crucial contribution to detect the injuries certainly caused by animal teeth. Highlights: A Jack Russel Terrier scavenged a significant portion of facial superficial and deep tissues. Application of advanced 3D processing and modelling techniques. Correlation between tissue injuries and 3D modelling.